Carotenoids present in goji berries Lycium barbarum L. are suitable to protect against mycotoxins effects: An in vitro study of bioavailability - Cristina Juan; Domenico Montesano; Jordi Mañes; Ana Juan-García (Journal of Functional Foods, 2022)
Bioactive compounds (BACs) in natural matrices are compartmented in specific anatomical structures resulting in low bioavailability. Here the study of bioavailability of carotenoids presents in Lycium barbarum L. goji berries (GB): zeaxanthin dipalmitate (ZDP), lutein (LUT), and zeaxanthin (ZEAX) using a trans-epithelial model with Caco-2 cells are presented. Among that the potential cytoprotection ZDP against beauvericin (BEA) mycotoxin in HepG2 cells was also carried out. Results revealed that the percentage of carotenoids from digested GB oscillated between 40 % and 98 % from 1 h to 4 h in differentiated Caco-2 cells for the most bioavailable carotenoids: LUT, ZEAX, and ZDP. The bioavailability of standard carotenoids at different concentrations was lower than those from natural digested GB. The disposition of GB carotenoids according to their bioavailability corresponds to ZDP > ZEAX > LUT. Cytoprotection of ZDP against beauvericin (BEA) in pretreatment strategy in HepG2 cells increased with the exposure time (from 24 h to 48 h) and the dose (BEA 1.25 µM to 2.5 µM); while in simultaneous, a decrease was observed with the time and an increase with the dose.